The Role of New Cities in the Developmental Balance of the Urban System“ Homs Province as a Case of Study ” - شيخ ديب سامي (Latakia University Journal -Engineering Sciences Series, 2020)
Several problems have emerged in the development process recently, the most important of which are the problems resulting from the growth of urban centers near existing cities, and thus this growth and spread has led to the imposition of its reality within the urban system and the emergence of differences in it. Some countries have followed the application of modern theories as an effective response to address the various problems, including the theory of new cities, which is considered one of theories of regional planning contributing to reducing the control of large cities by resettling residents and activities in new sites, and focusing development in them and then spreading it to the surrounding areas. Therefore, this theory appears to be one of the solutions that contribute to reducing developmental disparity and reducing the differences between centers and clusters in order to achieve the developmental balance of the urban system. Some international, Arab and local experiences have been studied to extract important results, and to study the possibility of applying them in the city of Homs and its surroundings within the province of Homs, due to its distinct location and importance in Syria.